Training Translational Scholars within Family Science Programs. - Sabatelli, Ronald M. (Family Relations (John Wiley & Sons, Inc.), 2017)
This article addresses issues related to the training of translational scholars in family science (FS) graduate programs. The article advances the view that (a) FS students need more direct socialization on how to message about and market the brand of their programs and (b) the FS brand should be organized around the centrality of translational expertise as one of the core goals of the training mission of FS programs. The article goes on to suggest that the training of translational scholars in FS programs should be organized around two interrelated initiatives. The first involves introducing coursework that balances the focus on the production of scholarship with a focus on the translation of this scholarship into policy and practice. The second is for FS programs to build their capacity to train translational scholars by creating “learning laboratories” in partnership with other health and social service programs, with the explicit goal of advancing collaborative practice and promoting interdisciplinary, multidisciplinary, transdisciplinary, and translational scholarship.